Material Moments in Virtual Worlds: Creating Hybrid Spaces for Feminist Consciousness-raising. Issue 3 (1st December 2022) - Abdul Rahim, Syafiqah; Walters, Hannah
Abstract: Covid-19 signalled rapid, near-wholesale shifts to the online world, yet how this affected the establishment of supportive, safe spaces for activism has received scant attention. Based on ongoing work with young women and girls in Malaysia, we discuss the pedagogic processes of feminist consciousness-raising as an informal mode of Girlhood Studies education and how online spaces might be reconfigured to enhance the virtual experience through hybrid workshops. Theorized from a feminist new materialist perspective and guided by the principles that feminism is an everyday practice, and feminism is for everybody, we argue that the hybrid space introduced material and sensory elements, facilitated feelings of connectedness, and helped establish a safe space for participants to engage with feminism and girls' rights in meaningful ways.